Polycarboxylic Acid-Based Deep Eutectic Solvents for Critical Metal Recovery from Lithium-Ion Batteries: Kinetic and Efficiency Analysis - Muryanta, Widya Aryani; Manaf, Azwar; Bahfie, Fathan; Handoko, Anton Sapto; Prasetyo, Erik (Trends in Sciences, 2025)
To meet the high demand for lithium-ion batteries (LIBs) and their corresponding challenges, effective and sustainable recycling methods are necessary. This research explores the use of deep eutectic solvents (DES) based on polycarboxylic acid to recover critical metals, such as lithium (Li), cobalt (Co), nickel (Ni), and manganese (Mn) from spent LIBs. The leaching efficiency of 3 DES was evaluated under various conditions by synthesizing them with succinic acid, malonic acid, and maleic acid using choline chloride. Optimal recovery was achieved with ChCl: Maleic acid, yielding 99.18 wt. % Li, 65.36 wt. % Co, 94.97 wt. % Ni, and 67.88 wt. % Mn at a S/L ratio of 20 g/L at 80 °C with constant stirring. Higher S/L ratios led to reduced recovery rates due to mass transfer limitations and solution saturation. Kinetic modeling revealed that the Jander model best described the leaching mechanism, suggesting a diffusion-controlled process. The activation energy calculation on DES ChCl: Maleic acid produces Li 38.57 kJ/mol, Co 63.09 kJ/mol, Ni 64.87 kJ/mol, and Mn 52.64 kJ/mol. The use of DES derived from eco-friendly polycarboxylic acids (succinic, malonic, and maleic acids) in this study represents an innovative way to recover critical metals from spent lithium-ion batteries (LIBs) in a sustainable and effective manner. Future studies are advised to examine the DES composition and investigate how agitation influences the recovery of specific metals. HIGHLIGHTS Lithium-ion battery leaching using deep eutectic solvent as leaching agent The results obtained from the leaching of lithium-ion batteries were the recovery of 99.18 % Li, 65.36 % Co, 67.88 % Mn, and 94.97 % Ni with the optimum leaching condition used was a solid/liquid ratio of 20gr/L with a temperature of 80 °C for 2 h. The kinetic mechanism of the leaching process follows Jander kinetics. GRAPHICAL ABSTRACT